Knowledge mapping of autophagy in chronic obstructive pulmonary disease from 2004 to 2024: a bibliometric analysis - Yating Zhang; Anqi Li; Sumei Xu; Haoge Liu (Frontiers in Medicine)
BackgroundChronic obstructive pulmonary disease (COPD) has become a major global healthcare issue due to its high prevalence and mortality rates. Increasing evidence suggests that autophagy plays a role in the development of COPD, yet there is a lack of bibliometric analyses on literature related to autophagy and COPD. Therefore, this study aims to summarize the current research status, research direction, and research hotspots in the literature related to COPD and autophagy.MethodsA search was conducted on the Web of Science Core Collection for literature related to COPD and autophagy from October 2004 to October 2024. Subsequently, bibliometric and visualization analyses were performed on the included publications using R software, CiteSpace, and VOSviewer.ResultsA total of 481 published articles across 229 journals related to COPD and autophagy were included. During the study period, there was a trend of continuous growth in both the annual number of publications and citations in this field. The United States had the highest centrality, while China was the most productive country. Major research institutions included Maastricht University, Harvard University, and Jikei University. The American Journal of Physiology-Lung Cellular and Molecular Physiology, International Journal of Chronic Obstructive Pulmonary Disease, and Autophagy are the most influential journals in this field. The author with the most published papers is Araya J, while Choi AMK is the most influential author. Frequently appearing keywords include “oxidative stress,” “obstructive pulmonary disease,” “aging,” “apoptosis,” and “mitophagy.”ConclusionThis bibliometric study helps researchers quickly understand the research overview of autophagy and COPD, thus providing new insights and directions for future research in this field.